Toward a Requisite Board Competencies Matrix. Issue 150 (March 2017) - Kravatzky, Axel
Abstract : Having a competent board is vital to every organization, but what does that mean? Here, Axel Kravatzky—in the first of a two‐part article—examines the necessary collective and individual competencies and advances in the design and use of Board Competency matrices.